(untitled) (CIPEEX, 2026)
Extraction of lower third molars is a frequent procedure in dental practice and can present varying degrees of complexity. The position and angulation of these teeth in relation to the mandibular ramus are determining factors for surgical planning, as they influence the difficulty of the procedure and the risk of complications. The objective of this study was to evaluate the angulation of impacted lower third molars in relation to the mandibular ramus using panoramic radiographs. A cross-sectional analytical study was conducted with 255 teeth from 141 patients over 19 years of age treated at the UniEVANGÉLICA Imaging Diagnostic Center. The images were evaluated by two calibrated examiners, according to the Pell & Gregory criteria and the Pederson index. Most patients were female (61.7%), with a mean age of 26.5 years. Regarding angulation, the mesioangular position predominated (36.1%), followed by distoangular (30.2%), horizontal (18.8%), and vertical (14.9%). It is concluded that mesioangular angulation was more prevalent, considering that the extraction of these teeth may require more complex surgical maneuvers, reinforcing the importance of radiographic evaluation in surgical planning.